Organization Of Experimental Works on The Development of Professional and Methodical Competence of Future Biology Teachers - Kuychiyeva Mujizakhan Abdumannobovna (Genius Journals, 2022)
The main purpose of the experimental work is to increase the level of compliance and expediency of the system of vocational education of students of pedagogical higher education institutions with the requirements of modern biological education. A variety of methods of collecting empirical data were used: observation of the pedagogical process in higher education institutions, individual interviews with teachers and students of higher education institutions; student and teacher questionnaires; analysis of pedagogical documents.
Keywords: vocational education; student and teacher questionnaires; education institutions; student